Microbial responses to plant functional types and historical resources additions in the shortgrass steppe - Bontti, Eliana E., author; Burke, Ingrid, advisor (Colorado State University. Libraries, 2009)
Nutrient addition in rangelands is an appealing way to increase plant biomass and quality, but little is known about the long-term effects of these additions on soil microbial activity and nutrient cycling. In addition, microbial activity may be affected by plant functional types (PFT) through influence on the levels of inorganic nitrogen (N) and labile carbon in the rhizosphere. This is particularly important in the shortgrass steppe (SGS), where plants with the C3 or C4 photosynthetic pathway differ in phenology, which affects the timing of maximum N uptake and root exudate production.

To understand the effect of PFT (C3 and C4 species) and historical nutrient additions on temporal patterns of N partitioning between microbes and plants, I estimated seasonal trends in plant biomass and N content, microbial N, and soil N availability. In addition, I evaluated monthly emissions of the greenhouse gases CO2 and N20, discriminating between fungal and bacterial production through incubations of soils under the influence of different PFTs and historical N additions. Last, I tested the effect of biosolid application on CO2 and N20 emissions from fungi and bacteria in SGS soils.

Seasonal trends in plant and microbial N concentration indicated that the two were synchronous during most of the plant growing season and both strongly influenced by precipitation. Plant functional type did not explain differences in microbial N and available soil N, but historical N amendments increased plant N content, decreased microbial N, and had no detectable effect on soil available N.

Fungi showed higher emissions of CO2 and N20 compared to bacteria in the SGS, whereas there was no difference in emissions between the two groups in the historically N amended plots. There were no effects of PFT on bacterial and fungal emissions of CO2 and N2O but high historical N fertilization resulted in increased CO2 and N2O emissions from bacteria.

Fungal emissions of CO2 were higher than bacterial emissions in SGS sites compared to biosolid amended sites, but I detected no differences between microbial groups in N20 emissions. CO2 and N20 emissions were higher in biosolid treated sites than non-treated SGS sites even 20 years after amendments ceased. Biosolid treated sites dominated by forbs showed higher C02 emissions compared to sites dominated by C3 grasses, while C3-dominated sites with high available inorganic N had higher N20 emissions than C4-dominated sites.

In summary, historical N additions had long lasting effects on SGS by increasing plant biomass and N. Given that N additions to ecosystems are increasing worldwide, it may be important to evaluate the impacts of these changes in processes on ecosystems services that grasslands provide. My results suggest that high levels of nutrient additions have unintended consequences such us increased CO2 and N20 emissions, and in particular carbon additions through biosolids increase fungal activity, which is also conducive to N2O production. These additions have a profound impact, since the elevated greenhouse gas emissions and changes in microbial communities last at least 20 years after the amendment was carried out.
Keywords: fungi; microbes; nitrogen; shortgrass steppe; ecology; microbiology; soil sciences